Comparative Analysis of Tracking Objects Using Optical Flow and Background Estimation on Silent Camera - Wahyu Supriyatin; Winda Widya Ariestya; Ida Astuti (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
Tracking and object is one of the utilizations on the field of the computer vision application. Object tracking utilization as a computer vision in this study is used to identify objects which exist within a frame and calculate the number of objects passing within a frame. The utilization of computer vision in various fields of application can be used to solve the existing problems. The method used in object tracking is by comparison between optical flow estimation method with background method. The test is conducted by using a still camera for both methods by making changes to the parameter values used as a reference. The results of the tests, conducted on the three video objects by comparing the two methods show a Total Recorded Time better than those of the background estimation method, being smaller than 100 seconds. Testing both methods successfully identifies the object tracking and calculates the number of passing cars.